Hybrid Learning for Educators and Students: A Review Study - Hamdan, Harim Izzati; Choo, Koo Ah; Shariman, Tenku Putri Norishah Tenku (International Journal of Membrane Science and Technology, 2023)
In this post COVID-19 pandemic era, Hybrid Learning (HL) has been identified as a proficient approach to education by many scholars. During the final stages of the pandemic, stakeholders in the education sector faced with the challenges to adapt and accommodate both in-person and online students simultaneously. Hybrid learning is now common to educators and students in higher education. The purpose of this paper is to examine the perception of educators and students on hybrid learning through the review of recent HL related literature. Literature suggests some challenges of HL for students and educators. The need for design of HL such as integrating the presence concept into hybrid classes is essential. Both parties’ viewpoints on HL can serve as an input for decision makers for better policies and outcomes on higher education systems, especially on hybrid and flexible learning. More research on the ‘presence’ concept are to be conducted to create a conducive HLE in the digital era.